Ethnobotany of Medicinal Plants of The Dawan Tribe Around Savanna of Mountain Mutis, Polen District, South Central Timor Regency - Obi Fandi Banfatin; Emilia Juliyanti Bria; Willem Amu Blegur (Universitas Sultan Ageng Tirtayasa, 2026)
The Mount Mutis Savanna is an area located in two government areas, namely South Central Timor Regency and North Central Timor Regency in East Nusa Tenggara, Indonesia. The tribes that inhabit this area are dominated by the Dawan tribe, whose lives are still relatively simple, utilizing natural resources to meet their daily needs. One thing that is quite popular is that people in this region use plants as traditional medicine. This research aims to determine the types of plants that have medicinal properties used by the Dawan tribe people around the Gunung Mutis Savannah, Polen District, South Central Timor Regency. The research methods used are observation, interviews, and documentation using qualitative and quantitative descriptive data analysis. The results of this research found 27 families of 38 plant species that are often used by the Dawan Tribe community in the Gunung Mutis Savanna, Polen District, South Central Timor Regency. The most widely used family is the Euphorbiaceae family, with a total of 5 plant species, namely Euphorbia tirucalli, Jatropha curcas, Jatropha gossypiifolia, Aleurites molucana, Euphorbia pulcherrima, and followed by the Zingiberaceae family with 3 species of plants, namely Kaempferia galangal, Curcuma longa, and Zingiber officinale. The dominant part of the plant used as medicine is the leaf organs and the dominant method of processing is by boiling and the highest consumption method is by drinking.